Bonding strength of multiple SiC die attachment prepared by sintering of Ag nanoparticles - Li, Jianfeng; Johnson, Christopher Mark; Buttay, Cyril; Sabbah, Wissam; Azzopardi, Stéphane (Elsevier, 2015)
3 mm × 3 mm dummy SiC dies with 100\200\200 nm thick Ti\W\Au metallization have simultaneously been attached using sintering of Ag nanoparticle paste on AlN-based direct bonded copper substrates with 5\0.1 μm thick NiP\Au finish. The effect of preparation and sintering parameters including time of drying the printed paste, sintering temperature and time, and pressure, on the average shear strength for multiple die attachments was investigated. The surfaces of the die attachments after the shear tests were observed and the individual shear strength values correlated with the “apparent” porosity and thicknesses of the corresponding die attachments (sintered layer). The results obtained are further discussed and compared with typical data reported in existing literature. Main conclusions include: (i) the present shear strength values and their variations are comparable with those reported for single die attachment samples, (ii) the effects of sintering parameters can be ascribed to the effectiveness of the organic content burnout and appropriate rate of growth and coalescence of the Ag nanoparticles during the sintering process, and (iii) thickness values of the sintered Ag die attachments may be taken as non-destructive measurements to monitor/evaluate the quality of die attachment during power electronic module manufacturing/assembly process.